Analisa Kepuasan Konsumen dan Loyalitas Konsumen terhadap Penjualan - Suyoto Arief; Nusa Dewa Harsoyo (University of Darussalam Gontor, 2015)
Economic fluctuations in Indonesia did not affect the food and beverage industry. A kind of the need to be was still being repaid because the community needed food. Food is the needs of primary must be fulfilled and cannot be influenced by the state of economy in indonesia. One of the famous traditional food business in Ponorogo is Jenang Mirah, industry is located in the village Josari, Jetis sub-district, district Ponorogo, East Java province. The industry has stood since tens of years ago, precisely around 1955. The name “Mirah” itself is taken from the name that the mother pioneering Mirah. Jenang glutinous rice traditional food is produced in ponorogo made of original material glutinous rice , coconut and sugar sugar, fruit and coconut milk coconut, without a preservative In 2013 on the day of Eid Jenang Mirah turnover rose sharply to 50% of H-7 - H + 7 because the number of orders and buyers from out of town or in the city. The request was evidenced by the number of subscribers since approximately 10 days before Idul Fitri. Jenang marketing strategy is now fairly easy, they do not need to bother distribute them to retailers. Because every day is a lot of traders who lined up to buy porridge ruby is the party to be sold again. This research using research field quantitative model with a method such as the spread of survey poll to consumers and interviews, samples used were obtained by using non-random sampling. Data were collected in two phases, the first to discover where the most preferred food by using the formula Weigthed Mean, then to analyze the link between customer satisfaction and loyalty and also between customer satisfaction and loyalty with sales. The results of the initial analysis using the Weighted Mean formula that serves as a determinant of superior products in Jenang Mirah is glutinous rice porridge with a value of 4.75. On further analysis showed that the correlation between customer satisfaction and loyalty shows the number (0.439) under 0.5 has a weak positive relationship, so when customer satisfaction is increased then the consumer loyalty in the company’s products will grow. And to influence consumer satisfaction and consumer loyalty to the figures showed sales (0,564) above 0.5 has a strong positive relationship in Jenang Mirah, so if the consumer satisfaction and enhanced customer loyalty then sales will increase because the number of goods that have been purchased by consumers and turnover the company increased. Finally, the author hopes this thesis will be beneficial for everyone, especially for the development of economic science in the field of marketing. And to the researchers next , is expected to meet a shortage of which is on a thesis is to conduct empirical research or research this can strengthen this study